A high corrosion resistance and high conductivity palladium / gold-plated palladium copper bonding wire and its production process

By forming a composite plating layer on the graphene copper alloy core of the bonded wire, the problem of bonded wire oxidation in the high temperature and high humidity environment in the prior art is solved, and the corrosion resistance and conductivity are achieved, and the product reliability is improved.

CN119153426BActive Publication Date: 2025-04-11SHANGHAI WONSUNG ALLOY MATERIAL CO LTD

Patent Information

Application Number
CN202411604110.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-04-11
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing bonded wires are easily oxidized under high temperature and high humidity environments, which affects their conductivity and reliability. The primary cell reaction between the palladium layer and the copper core after the coating is damaged further reduces product reliability.

Method used

A graphene copper alloy core is used and a composite coating is formed on its surface, including a first palladium layer, an intermediate gold layer, a second palladium layer and a top gold layer. By improving the design of the core material and coating, the corrosion resistance and electrical conductivity of the bonded wire are improved.

Benefits of technology

It significantly improves the corrosion resistance and conductivity of bonded wires, reduces oxidation risks and primary cell reactions, and improves the high-temperature reliability and service performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153426B_ABST
    Figure CN119153426B_ABST
Patent Text Reader

Abstract

The present invention discloses a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire and a production process thereof, and relates to the technical field of bonding wires. In order to improve the corrosion resistance of the bonding wire, the present invention improves the bonding wire by modifying the core material and preparing a composite coating. The present invention first improves the core layer, and by adding graphene to the core layer, the corrosion potential of the core material is greatly improved, and the copper core has good heat dissipation performance and high-temperature electrical conductivity, thereby avoiding heat accumulation and temperature rise in the bonding wire. On this basis, the present invention also improves the coating, and by reducing the metal ion concentration in the plating solution, adding a hole-filling agent, and performing pulse current electroplating, the surface morphology of the electroplated coating is improved, and by annealing, a diffusion layer is formed between the graphene copper alloy core and different electroplated layers, thereby improving the mutual bonding strength and improving the performance of the bonding wire.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bonding wires, in particular to a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire and a production process thereof. Background Art

[0002] Bonding wire is one of the key components in semiconductor packaging. It is mainly used to connect the pads on the semiconductor chip and the external pins or package base to achieve electrical connection. Due to the high concentration of electronic components, the heat generated is also greater. The increase in heat often has a huge impact on the conductivity of the bonding wire. Due to the wide range of applications, the bonding wire also needs to remain stable under various environmental conditions, such as temperature, humidity and other external factors, to prevent oxidation in high temperature and high humidity environments, which affects its conductivity and reliability.

[0003] Therefore, in order to achieve the above goals, the current mainstream technology mostly uses oxygen-free copper as the core material, and deposits a uniform palladium layer on the surface of the core material by electroplating or chemical plating, so as to avoid oxidation of the copper wire during welding operations and improve the welding performance of the core material and the stability after welding; however, after the coating is damaged, a primary battery reaction is likely to occur between the palladium layer and the copper core, which further causes a decrease in product reliability and affects product use. Summary of the invention

[0004] The object of the present invention is to provide a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire and a production process thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solution: a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire, having the following technical features: the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire is composed of a graphene copper alloy core and a composite coating coated on the outside of the graphene copper alloy core;

[0006] The diameter of the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire is 15-500 μm, and the thickness of the composite coating is 51-185 nm;

[0007] The composite coating consists of a first palladium layer, a middle gold layer, a second palladium layer and a top gold layer from bottom to top.

[0008] Furthermore, the grain size within the interface of the graphene copper alloy core is 0.1-200 μm;

[0009] The graphene copper alloy core contains 100-10000ppm of graphene and 5-5000ppm of reinforcing metal material;

[0010] Among them, the reinforcing metal material is any one or more of Ag, Pd, Au, Pt, Li, P, Ca, Ni, Be, Y, La, Ce, Zr, In, Ge, and Sc.

[0011] Furthermore, the graphene copper alloy core contains 300-3000ppm of graphene and 0-3000ppm of reinforcing metal material;

[0012] The reinforcing metal material is any one or more of Au, Pd, In, P, Ni, Ca, Li, and Sc;

[0013] When the reinforcing metal material contains any one of P, Li and Sc, the single component addition amount of P, Li and Sc is 0-300ppm.

[0014] Furthermore, in the composite coating, the thickness of the first palladium layer is 10-20 nm, the thickness of the middle gold layer is 20-80 nm, the thickness of the second palladium layer is 20-80 nm, and the thickness of the top gold layer is 1-5 nm.

[0015] Furthermore, a method for preparing a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire comprises the following steps:

[0016] S1. Preparation of graphene copper alloy core;

[0017] S11. The graphene copper mixed raw material is protected by a nitrogen atmosphere, placed in an environment of 40-80°C and dried for 1-12 hours, and then pressed into a blank, placed in an SPS sintering furnace, protected by an argon atmosphere, and a pressure of 100-1000 kN is applied to the blank, and the temperature is raised to 900-1200°C at a rate of 90-110°C / min, sintered into a block, and then cooled to room temperature with the furnace to obtain a graphene copper alloy original ingot;

[0018] S12. Mixing the graphene copper alloy ingot with the reinforcing metal material, protecting the ingot with argon atmosphere, heating the induction furnace to 1050-1250°C for melting, stirring and mixing for 10s-15min, and then continuously casting the molten metal into a mother rod with a diameter of 8mm;

[0019] S13. The mother rod is subjected to multiple drawing and elongation treatments until its diameter is 15-500 μm to obtain a graphene copper alloy core;

[0020] S2. Preparing a composite coating;

[0021] S21. Preparing a first palladium layer;

[0022] Place the cleaned graphene copper alloy core in the first electroplating palladium solution at a temperature of 70-75°C and set the pulse current to 3-5 mA / cm 2, the on-time of each pulse is 0.5-1s, and the off-time is 0.5-2s. After electroplating to the required thickness of the first palladium layer, the pulse is stopped, the graphene copper alloy core is taken out, and the first palladium layer is formed after washing and drying;

[0023] S22. Preparing an intermediate gold layer;

[0024] Place the graphene copper alloy core treated in step S21 in an intermediate gold plating solution at a temperature of 70-80°C, and set the electroplating pulse current to 5-15 mA / cm 2 , the on-time of each pulse is 1.5-3s, and the off-time is 0.5-2s. After electroplating to the required thickness, the pulse is stopped, the graphene copper alloy core is taken out, and after washing and drying, an intermediate gold layer is formed;

[0025] S23. Place the graphene copper alloy core treated in step S22 in a second palladium electroplating solution at a temperature of 70-80°C and set the current to 10-60 mA / cm 2 , after electroplating to a desired thickness, the graphene copper alloy core is taken out, washed and dried to form a second palladium layer;

[0026] S24. Place the graphene copper alloy core processed in step S23 in a top layer gold plating solution at a temperature of 70-80°C and set the current to 10-60 mA / cm 2 , after electroplating to a desired thickness, the graphene copper alloy core is taken out, washed and dried, and a top gold layer is formed to obtain a graphene copper alloy core with a composite coating;

[0027] S3. The graphene copper alloy core with the composite coating is annealed at a temperature of 400-700°C, a furnace length of 600-1000mm, and an annealing speed of 40-140m / min. After the annealing, a high corrosion resistance and high conductivity palladium-plated / gold-plated palladium-copper bonding wire is obtained.

[0028] Furthermore, the method for preparing the graphene copper mixed material comprises the following steps:

[0029] a1. Prepare electrolyte;

[0030] Copper sulfate, sulfuric acid and deionized water are mixed to prepare a mixed solution with a sulfuric acid concentration of 10-200 g / L and a copper ion concentration of 10-100 g / L, 1-20 g / L of graphene is added to the electrolyte, and the graphene is evenly dispersed by electromagnetic stirring and ultrasonic dispersion to obtain an electrolyte;

[0031] b1. Use high-purity copper with impurity element content of 0-10ppm as anode and pure copper plate as cathode for electroplating. The voltage is 2-10V and the current density is 1-10mA / cm 2After 10-60 minutes of electro-deposition, the cathode is taken out and washed with deionized water, and the graphene copper powder on the cathode surface is collected and dried. After XPS detection, it is determined that the carbon-copper bond ratio is 35-45%, and then it is mixed with oxygen-free copper powder. After that, it is melted evenly in an argon atmosphere, cooled, and XPS detection is performed again. After determining that the carbon-copper bond ratio is 3-5%, it is mixed with pure copper powder again. After melting evenly, it is crushed by ball milling to obtain a graphene copper mixed material.

[0032] Furthermore, the method for preparing the graphene copper mixed material comprises the following steps:

[0033] a2. Disperse the graphene in ultrapure water, stir and ultrasonically disperse and wash for 0.5-1h, then filter and filter, repeat 2-3 times, detect the pH value of the filtrate, confirm that the pH value is in the range of 6.3-7 for qualified cleaning, otherwise repeat the above steps to wash the graphene with ultrapure water until the pH value of the filtrate is qualified, dry the washed graphene in a nitrogen atmosphere, cool and set aside;

[0034] b2. After the cleaned graphene is mixed with high-purity oxygen-free copper powder, low-temperature plasma ball milling is performed for 3-24 hours. The speed during ball milling is 100-1200rpm, the protective gas is nitrogen, and the plasma working power is 10-400W. After the ball milling, a graphene-copper mixed material is obtained.

[0035] Furthermore, the first palladium electroplating solution includes palladium tetraaminoacetate, p-carboxybenzenesulfonamide and a composite pore-filling agent;

[0036] Wherein, in the first palladium electroplating solution, the concentration of palladium tetraaminoacetate is 3-5 g / L, the concentration of p-carboxybenzenesulfonamide is 5-15 mg / L, and the concentration of the composite pore filling agent is 25-55 mg / L;

[0037] The composite pore-filling agent is a composition of diethyl dithiophosphate ammonium salt and L-alanine benzyl ester p-toluenesulfonate in a mass ratio of 1:1;

[0038] The second palladium electroplating solution comprises tetraaminopalladium dichloride, p-carboxybenzenesulfonamide and β-cyanoalanine;

[0039] Wherein, in the second palladium electroplating solution, the concentration of tetraaminopalladium dichloride is 5-10 g / L, the concentration of p-carboxybenzenesulfonamide is 5-10 mg / L, and the concentration of β-cyanoalanine is 10-20 mg / L;

[0040] The intermediate gold plating solution includes gold cyanide and a composite hole filling agent;

[0041] Among them, in the intermediate gold plating solution, the concentration of gold cyanide is 4-8g / L, and the concentration of the composite hole filling agent is 50-80mg / L;

[0042] The top layer gold plating solution includes gold cyanide, and the concentration of gold cyanide is 5-15g / L;

[0043] Wherein, when the intermediate gold plating solution and the top layer gold plating solution are used, the pH value is adjusted to 10-12 by ammonia water.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] In order to improve the corrosion resistance of the bonding wire, the present invention improves the bonding wire by modifying the core material and preparing a composite coating;

[0046] The present invention first improves the core layer by adding graphene to the core layer and calcining it to form a core material. In this way, the metal covalent bonds formed between the graphene and the copper substrate are evenly distributed, thereby greatly improving the corrosion potential of the core material, reducing the corrosion current, and reducing the weight loss caused by halogen corrosion. In addition, due to the even distribution of the metal covalent bonds formed between the graphene and the copper substrate, the copper core has good heat dissipation performance and high-temperature electrical conductivity, so that the electrical conductivity of the bonding wire prepared by the present invention is more than 30% higher than that of traditional oxygen-free copper at 150°C.

[0047] In addition, graphene itself has extremely high thermal conductivity, which can accelerate the conduction of heat and prevent the accumulation of heat in the bonding wire, thus further improving the high-temperature reliability of the product. Also, due to the addition of graphene, the grain structure in the copper core is improved, which can effectively inhibit the growth of intermetallic compounds and improve the working performance of the bonding wire.

[0048] On this basis, the present invention also improves the coating;

[0049] The present invention firstly performs wire drawing and refining treatment on the graphene copper alloy core before electroplating the composite coating, so as to avoid stress damage to the electroplating layer caused by wire drawing after the subsequent preparation of the plating layer, thereby affecting the bonding strength between the coating and the graphene copper alloy core. The coating prepared by the present application is a composite coating. When preparing the bottom coating, i.e., the first palladium layer and the middle gold layer, the present application defines the electroplating solution and the electroplating method thereof. By reducing the metal ion concentration in the electroplating solution, adding a pore filling agent and using a pulse current electroplating method, the bottom electroplating layer can effectively electroplate and smooth the surface of the graphene copper alloy core after the wire drawing treatment. The addition of the composite pore filling agent can effectively improve and avoid the roughness after wire drawing. The tip discharge phenomenon on the surface causes tiny holes to appear in the electroplating layer, and the lower metal ion concentration and pulse current can effectively improve the deposition rate of the metal layer during electroplating and reduce the defects during deposition of the plating layer; after the first palladium layer and the intermediate gold layer are leveled, the surface is electroplated again with a large current, which can effectively improve the electroplating efficiency and accelerate the production speed. In addition, the present invention further anneals the bonding wire after preparing the electroplating layer, so that the wire eliminates the processing stress and reorganizes the grains. In addition, this process can form a diffusion layer between the graphene copper alloy core and different electroplating layers, improve the mutual bonding strength, avoid the peeling of the coating, and improve the performance of the bonding wire. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a diagram of the grain structure within the interface of the graphene copper alloy core prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The operation methods of Examples 1-30 and Comparative Examples 1-5 in this application are as follows:

[0053] A method for preparing a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire comprises the following steps:

[0054] S1. Preparation of graphene copper alloy core;

[0055] S11. The graphene copper mixed raw material is protected by a nitrogen atmosphere, placed in an environment of 80°C for drying for 8 hours, pressed into a blank, placed in an SPS sintering furnace, protected by an argon atmosphere, and after applying a pressure of 800 kN to the blank, the temperature is raised to 1000°C at a rate of 100°C / min, sintered into a block, and then cooled to room temperature with the furnace to obtain a graphene copper alloy original ingot;

[0056] Wherein, the preparation method of the graphene copper mixed material is:

[0057] a2. The graphene was dispersed in ultrapure water, electromagnetically stirred and ultrasonically dispersed for 1h, filtered and filtered, repeated 3 times, the pH value of the filtrate was detected, and the pH value was confirmed to be in the range of 6.3-7 for cleaning. Otherwise, the above steps were repeated to wash the graphene with ultrapure water until the pH value of the filtrate was qualified, and the washed graphene was dried in a nitrogen atmosphere and cooled for use;

[0058] b2. After the cleaned graphene was mixed with high-purity oxygen-free copper powder, low-temperature plasma milling was performed for 12h, the milling speed was 800rpm, the protective gas was nitrogen, the plasma operating power was 120W, and after the milling, a graphene copper mixed material was obtained;

[0059] S12. The graphene copper alloy ingot is mixed with the reinforcing metal material, and the mixture is heated to 1200°C by electromagnetic induction for melting under argon atmosphere protection. After stirring and mixing for 3 minutes, the molten metal is continuously cast into a mother rod with a diameter of 8 mm;

[0060] S13. The mother rod is subjected to multiple drawing and elongation treatments until its diameter is 15-500 μm to obtain a graphene copper alloy core;

[0061] S2. Preparing a composite coating;

[0062] S21. Preparing a first palladium layer;

[0063] The cleaned graphene copper alloy core was placed in the first electroplating palladium solution at a temperature of 70°C and the pulse current was set to 3 mA / cm 2 , each pulse has an on-time of 0.5s and an off-time of 1.5s. After electroplating to the required thickness of the first palladium layer of 20nm, the pulse is stopped, the graphene copper alloy core is taken out, and the first palladium layer is formed after washing and drying;

[0064] Wherein, in the first palladium electroplating solution, the concentration of palladium tetraaminoacetate is 4 g / L, the concentration of p-carboxybenzenesulfonamide is 8 mg / L, and the concentration of the composite pore filling agent is 30 mg / L;

[0065] The composite pore-filling agent is a composition of diethyl dithiophosphate ammonium salt and L-alanine benzyl ester p-toluenesulfonate in a mass ratio of 1:1;

[0066] S22. Preparing an intermediate gold layer;

[0067] The graphene copper alloy core treated in step S21 is placed in an intermediate gold plating solution at a temperature of 75°C, and the electroplating pulse current is set to 10 mA / cm 2, each pulse is on for 1.5s, off for 1.5s, after electroplating until the thickness of the middle gold layer is 80nm, stop the pulse, take out the graphene copper alloy core, wash and dry it, and form the middle gold layer;

[0068] Wherein, in the intermediate gold plating solution, the concentration of gold cyanide is 4-8g / L, the concentration of the composite hole filling agent is 50-80mg / L, and ammonia water is used to adjust the pH value to 11 during use;

[0069] S23. Place the graphene copper alloy core treated in step S22 in a second palladium electroplating solution at a temperature of 75°C and set the current to 50 mA / cm 2 , after electroplating until the second palladium layer has a thickness of 80 nm, the graphene copper alloy core is taken out, and after washing and drying, a second palladium layer is formed;

[0070] Wherein, in the second palladium electroplating solution, the concentration of tetraaminopalladium dichloride is 10 g / L, the concentration of p-carboxybenzenesulfonamide is 8 mg / L, and the concentration of β-cyanoalanine is 15 mg / L;

[0071] S24. Place the graphene copper alloy core processed in step S23 in a top layer gold plating solution at a temperature of 80°C and set the current to 15 mA / cm 2 , after electroplating until the gold layer thickness is 5 nm, the graphene copper alloy core is taken out, washed and dried to form a top gold layer, and a graphene copper alloy core with a composite coating is obtained;

[0072] In the top layer gold plating solution, the concentration of gold cyanide is 12 g / L, and ammonia water is used to adjust the pH value to 11 during use;

[0073] S3. The graphene copper alloy core with the composite coating is annealed at a temperature of 600°C, a furnace length of 800 mm, and an annealing speed of 40 m / min. After the annealing, a high corrosion-resistant and high-conductivity palladium-plated / gold-plated palladium-copper bonding wire is obtained.

[0074] The operating method of Example 31 in this application is as follows:

[0075] A method for preparing a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire comprises the following steps:

[0076] S1. Preparation of graphene copper alloy core;

[0077] S11. The graphene copper mixed raw material is protected by a nitrogen atmosphere, placed in an environment of 80°C for drying for 8 hours, pressed into a blank, placed in an SPS sintering furnace, protected by an argon atmosphere, and after applying a pressure of 800 kN to the blank, the temperature is raised to 1000°C at a rate of 100°C / min, sintered into a block, and then cooled to room temperature with the furnace to obtain a graphene copper alloy original ingot;

[0078] Wherein, the preparation method of the graphene copper mixed material is:

[0079] a1. Prepare electrolyte;

[0080] Copper sulfate, sulfuric acid and deionized water are mixed to prepare a mixed solution with a sulfuric acid concentration of 120 g / L and a copper ion concentration of 50 g / L, 5.8 g / L of graphene is added to the electrolyte, and the graphene is evenly dispersed by electromagnetic stirring and ultrasonic dispersion to obtain an electrolyte;

[0081] b1. Using high-purity copper with an impurity element content of 4ppm as the anode and a pure copper plate as the cathode, electroplating was performed with a voltage of 6V and a current density of 2mA / cm 2 After 40 minutes of electro-deposition, the cathode was taken out and washed with deionized water, and the graphene copper powder on the cathode surface was collected. After drying, the graphene copper powder was subjected to XPS detection. After determining that the carbon-copper bond ratio was 35-45%, the graphene copper powder was mixed with oxygen-free copper powder, and then melted evenly in an argon atmosphere. After cooling, the graphene copper powder was subjected to XPS detection again, and after determining that the carbon-copper bond ratio was 3-5%, the graphene copper powder was mixed with pure copper powder again. After melting evenly, the graphene copper mixed material was obtained by ball milling.

[0082] S12. The graphene copper alloy ingot is mixed with the reinforcing metal material, and the mixture is heated to 1200°C by electromagnetic induction for melting under argon atmosphere protection. After stirring and mixing for 3 minutes, the molten metal is continuously cast into a mother rod with a diameter of 8 mm;

[0083] S13. The mother rod is subjected to multiple drawing and elongation treatments until its diameter is 15-500 μm to obtain a graphene copper alloy core;

[0084] S2. Preparing a composite coating;

[0085] S21. Preparing a first palladium layer;

[0086] The cleaned graphene copper alloy core was placed in the first electroplating palladium solution at a temperature of 70°C and the pulse current was set to 3 mA / cm 2 , each pulse has an on-time of 0.5s and an off-time of 1.5s. After electroplating to the required thickness of the first palladium layer of 20nm, the pulse is stopped, the graphene copper alloy core is taken out, and the first palladium layer is formed after washing and drying;

[0087] Wherein, in the first palladium electroplating solution, the concentration of palladium tetraaminoacetate is 4 g / L, the concentration of p-carboxybenzenesulfonamide is 8 mg / L, and the concentration of the composite hole filling agent is 30 mg / L;

[0088] The composite pore-filling agent is a composition of diethyl dithiophosphate ammonium salt and L-alanine benzyl ester p-toluenesulfonate in a mass ratio of 1:1;

[0089] S22. Preparing an intermediate gold layer;

[0090] The graphene copper alloy core treated in step S21 is placed in an intermediate gold plating solution at a temperature of 75°C, and the electroplating pulse current is set to 10 mA / cm 2 , each pulse is on for 1.5s, off for 1.5s, after electroplating until the thickness of the middle gold layer is 80nm, stop the pulse, take out the graphene copper alloy core, wash and dry it, and form the middle gold layer;

[0091] Wherein, in the intermediate gold plating solution, the concentration of gold cyanide is 4-8g / L, the concentration of the composite hole filling agent is 50-80mg / L, and ammonia water is used to adjust the pH value to 11 during use;

[0092] S23. Place the graphene copper alloy core treated in step S22 in a second palladium electroplating solution at a temperature of 75°C and set the current to 50 mA / cm 2 , after electroplating until the second palladium layer has a thickness of 80 nm, the graphene copper alloy core is taken out, and after washing and drying, a second palladium layer is formed;

[0093] Wherein, in the second palladium electroplating solution, the concentration of tetraaminopalladium dichloride is 10 g / L, the concentration of p-carboxybenzenesulfonamide is 8 mg / L, and the concentration of β-cyanoalanine is 15 mg / L;

[0094] S24. Place the graphene copper alloy core processed in step S23 in a top layer gold plating solution at a temperature of 80°C and set the current to 15 mA / cm 2 , after electroplating until the gold layer thickness is 5 nm, the graphene copper alloy core is taken out, washed and dried to form a top gold layer, and a graphene copper alloy core with a composite coating is obtained;

[0095] In the top layer gold plating solution, the concentration of gold cyanide is 12 g / L, and ammonia water is used to adjust the pH value to 11 during use;

[0096] S3. The graphene copper alloy core with the composite coating is annealed at a temperature of 600°C, a furnace length of 800 mm, and an annealing speed of 40 m / min. After the annealing, a high corrosion-resistant and high-conductivity palladium-plated / gold-plated palladium-copper bonding wire is obtained.

[0097] In the present application, the reinforcing metal material used in the embodiments and comparative examples is any one or more of Ag, Pd, Au, Pt, Li, P, Ca, Ni, Be, Y, La, Ce, Zr, In, Ge, and Sc;

[0098] The components of Examples 1-31 and Comparative Examples 1-5 of the present application are shown in Table 1 and Table 2 below:

[0099] Table 1.

[0100]

[0101] Table 2.

[0102]

[0103] The above embodiments and comparative examples were tested for performance;

[0104] High temperature oxidation resistance test: the core material is processed to 0.8mil, and the Kulisuo KS ProCuPLUS wire bonding machine is used for normal wire bonding, the welding size is 35μm in diameter, the pad temperature is 220°, and the pad is kept warm for 2 minutes after welding; a 200x optical microscope is used to check the color of the solder balls; if 1 / 3 of the solder balls are red or black, it is unqualified; if the solder balls are red as a whole, it is fair; if the solder balls are light yellow, it is qualified; if more than 80% of the solder balls are silver-white, and the number of light yellow solder balls is less than 5%, it is good; if all the solder balls are silver-white, it is excellent;

[0105] FAB inspection: Process the core material to 0.8mil, use the Kulisuo method KS ProCuPLUS wire bonding machine to burn empty balls, EFO conditions are current 60mA, time 200μs, EFO GAP 30mil, tail elongation 10mil, nitrogen and hydrogen mixed gas protection-flow rate 0.5L / min, check the diameter distribution and whether the ball is round, the target ball diameter is 34um, check the standard deviation, check whether the ball shape is round, and whether there is eccentricity; during the inspection, 100 pieces of empty balls, the ball diameter standard deviation greater than 1.0 is unqualified, the standard deviation is within 0.7-1 is fair; the standard deviation is within 0.5-0.7 is qualified, the standard deviation is within 0.3-0.5 is good, and the standard deviation is less than 0.3 is excellent;

[0106] HAZ detection: the core material is processed to 0.8mil, and the Kulisuo KS ProCuPLUS wire bonding machine is used to burn the empty burning ball. The EFO conditions are current 60mA, time 200μs, EFO GAP 30mil, tail elongation 10mil, nitrogen and hydrogen mixed gas protection-flow rate 0.5L / min; take a standard length of empty burning ball, use carbon tape to stick it to the aluminum sample table, use argon ion polishing instrument, 15° purge for 30min; after the processed sample, use SEM to check the length of the heat affected zone (HAZ), with the grains not recrystallized as the boundary; during the test, HAZ length greater than 150um is unqualified, between 130-150um is fair, between 110-130μm is qualified, HAZ length between 90-110um is good, and HAZ length less than 90um is excellent;

[0107] Long wire arc shape detection: the core material is processed to 0.8mil, and a 10mm long wire arc is punched using the Kulisuo KS ProCuPLUS wire punching machine. The SEM is used to check the offset between the wire arc and the target straight line. If the deviation from the target straight line is 1.5 times the wire diameter, it is considered offset. During the inspection, if it is more than 2 times the wire diameter, it is unqualified; if it is within 1.5-2 times the wire diameter, it is fair; if it is within 1.3-1.5 times the wire diameter, it is qualified; if it is within 1.1-1.3 times the wire diameter, it is good; if it is within 1.1 times the wire diameter, it is excellent.

[0108] One-point thrust test: Process the core material to 0.8mil, use the KS ProCuPLUS wire bonding machine of the Kulisuo method, wire bond normally, and then use the TST-8300D push-pull tester to push off the solder ball of 1 solder joint to measure the thrust. The larger the thrust value, the better. During the test, if the thrust is less than 12g, it is unqualified; if the thrust is between 12-14g, it is fair; if the thrust is between 14-16g, it is qualified; if the thrust is between 16-20g, it is good; if the thrust is greater than 20g, it is excellent.

[0109] Two-point tension test: Process the core material to 0.8mil, use the KS ProCuPLUS wire bonding machine with the Kulisuo method, wire bond normally, and then use the TST-8300D push-pull tester to hook the vertex of the wire arc to measure the two-point tension. The larger the push value, the better. During the test, if the two-point tension is less than 3g, it is unqualified, between 3-4g is fair, the two-point tension is between 4-5g, it is qualified, the two-point tension is based on 5-6g, it is good, and the two-point tension is greater than 6g, it is excellent.

[0110] Cutter wear detection: The core material is processed to 0.8mil, and the Kulisuo KS ProCuPLUS wire bonding machine and SPTSU-25063-303F-RU34TP chopper are used for normal wire bonding. After 40W points of wire bonding, a high-power microscope is used to check the ball morphology and fishtail morphology of a solder joint, and then SEM is used to observe the wear morphology of the CD area at the mouth of the chopper. The ball size is complete, the protein is uniform, and the fishtail is uniform without missing corners. The smaller the wear of the CD area, the better the performance; during the test, the fishtail width is less than 1.5 times the line width, which is unqualified; between 1.5-2 times is fair, between 2-2.5 times is qualified, between 2.5-3 times is good, and between 2.5 times and 3 times is excellent;

[0111] Aluminum extrusion inspection: Process the core material to 0.8mil, use the Kulisuo KS ProCuPLUS wire bonding machine and SPT SU-25063-303F-RU34TP splitter to perform normal wire bonding, and use a high-power microscope to check the size of the aluminum extrusion. The smaller the size, the better. During the inspection, if the Al extrusion size exceeds 2.5 times the wire diameter, it is unqualified; if the Al extrusion size is within 2-2.2 times the wire diameter, it is fair; if the Al extrusion size is within 1.9-2 times the wire diameter, it is qualified; if the Al extrusion size is within 1.8-1.9 times the wire diameter, it is good; if the Al extrusion size is within 1.8 times the wire diameter, it is excellent;

[0112] Crater detection: Process the core material to 0.8mil, use the Kulisuo KS ProCuPLUS wire bonding machine, SPT SU-25063-303F-RU34TP splitter, adjust the power to the highest point to perform wire bonding; observe whether the chip pad is damaged after bonding with the bonding ball; before observation, use a mixture of nitric acid and hydrochloric acid to remove the bonding ball without affecting the chip; after removing the bonding wire, if there are obvious visible pits on the silicon layer, use a knife to scratch around the solder ball and feel obvious pits, it is a serious defect and unqualified; there are slight pit marks on the aluminum layer, use a knife to scratch around the solder ball and touch without obvious pits, it is Slight defects, qualified; the silicon layer surface is smooth without pit marks, qualified; during the test, use a knife to scratch around the solder ball and feel obvious pits, which is a serious defect and unqualified; there are slight pits on the aluminum layer, and there are no obvious pits when using a knife to scratch around the solder ball, which is a slight defect; the proportion of slight pits in the number of test chips is more than 25%, which is fair; the proportion of slight pits in the number of test chips is within 5-10%, which is qualified; the proportion of slight pits in the number of test chips is within 5%, which is good, and the silicon layer surface is smooth without pit marks, which is excellent;

[0113] Hast test: the core material is processed to 0.8mil, and the KS ProCuPLUS wire bonding machine and SPT SU-25063-303F-RU34TP splitter are used. After normal wire bonding and plastic sealing, 23 pieces are subjected to the high pressure cooking test accelerated test (HAST, the test condition temperature is 130℃, 85%RH); after completing the accelerated test, the 23 pieces are required to pass the OS open and short circuit tests. Failure of 192H is unqualified, passing 192H is fair, 480H is qualified, 672H is good, and 864H is excellent;

[0114] Conductivity test: Cut 1m of finished wire, use a laser diameter gauge to measure the wire diameter, and then measure its resistance at an ambient temperature of 20℃ and 100℃ respectively: room temperature resistance greater than 2.4μΩ.cm is unqualified; room temperature resistance less than 1.9μΩ.cm and high temperature resistivity less than 2.4μΩ.cm are fair; room temperature resistance less than 1.85μΩ.cm and high temperature resistance less than 2.3μΩ.cm are qualified; room temperature resistance less than 1.8μΩ.cm and high temperature resistance less than 2.2μΩ.cm are good; room temperature resistance less than 1.75μΩ.cm and high temperature resistance less than 2.0μΩ.cm are excellent;

[0115] The test results are shown in Tables 3 and 4 below. The test results are shown from left to right, from bad to good: a→b→c→d→e;

[0116] Among them, a corresponds to unqualified, b corresponds to average, c corresponds to qualified, d corresponds to good, and e corresponds to excellent;

[0117] Table 3.

[0118] Sample name High temperature oxidation resistance FAB form HAZ length Long arc pattern A little push Two-point tension Rifling knife wear Aluminum Extrusion crater hast Electrical conductivity Comparative Example 1 a d b b c b d e e b d Comparative Example 2 a d b b c b d e e b d Comparative Example 3 a d b b c b d e e b d Comparative Example 4 a d b b c b d e e b d Comparative Example 5 a d b b c b d e e b d Implementation 1 a c b b b b e e e b d Implementation 2 b c b b b c e e e b d Implementation 3 b c c c c c e e e c d Implementation 4 c d c c c d e e e c e Implementation 5 c d d d d d e d d d e Implementation List 6 d d d d d e d d d d e Implementation List 7 d e e e e e d d d e e Implementation 8 e e e e e e d c c e e Implementation List 9 e e e e e d d c c e e Implementation 10 e d e e e c d c c e e Implementation 11 c d d d d d e e e c c Implementation 12 d d d d d d e e e d c

[0119] Table 4.

[0120] Sample name High temperature oxidation resistance FAB form HAZ length Long arc pattern A little push Two-point tension Rifling knife wear Aluminum Extrusion crater hast Electrical conductivity Implementation 13 e e c e d d e e e c c Implementation 14 c d d d d d e e e e c Implementation 15 d e e e e d e e e e b Implementation 16 e e e d d c e e e d b Implementation 17 d d e d d d d e d d d Implementation 18 d e e e d d d e d d b Implementation column 19 e e e d d e e e e e a Implementation 20 d e d d d e e e e d d Implementation 21 d e e d d d e d d e d Implementation column 22 e e e e e d d d d e d Implementation 23 d e d d d e e d d d d Implementation column 24 e d d d d e d d d e d Implementation 25 e d e e d d d c c e c Implementation column 26 d d d d d e e d d d d Implementation column 27 e e d e d e d e e e e Implementation 28 e e e e e e d d d e e Implementation 29 e e e e e e d d d e c Implementation 30 d e c e c e d e d c e Implementation 31 b c c c c c e e e c d

[0121] Comparative Examples 6-8 are also provided;

[0122] Compared with Example 1, in Comparative Example 6, no composite hole filling agent is added to the first palladium electroplating solution and the intermediate gold plating solution;

[0123] Comparative Example 7 Compared with Example 1, in this comparative example, no pulse current electroplating was used when electroplating the first palladium layer and the middle gold layer;

[0124] Comparative Example 8 Compared with Example 1, in this comparative example, when electroplating the first palladium layer and the middle gold layer, no composite hole filling agent was used and no pulse current electroplating was used;

[0125] The bonding wires prepared in Example 1 and Comparative Examples 6-8 were drawn again, with a drawing elongation of 12%, and then tested after drawing;

[0126] An optical microscope was used to examine the appearance morphology of the coatings in Example 1 and Comparative Examples 6-8;

[0127] The bonding wires prepared in Example 1 and Comparative Examples 6-8 were subjected to a relative bending-straightening test repeated 50 times, and the bending portion presented a semicircle with a diameter of 1 cm. After the test, the appearance of the coating was checked;

[0128] The inspection results are shown in Table 5 below;

[0129] Table 5.

[0130] Example 1 Comparative Example 6 Comparative Example 7 Comparative Example 8 Appearance Smooth and bright surface Smooth and bright surface Smooth and bright surface Slight streaking Appearance of coating after bending resistance No cracks or peeling of the coating at the bend The coating cracks at the bend without peeling The coating cracks at the bend without peeling Partial peeling of the coating at the bend

[0131] The microscopic grain size test was also performed on the cross section of Example 1. The test results are shown in Figure 1 .

[0132] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire, characterized in that: The following steps are involved: S1. Preparation of graphene copper alloy core; S11. The graphene copper mixed raw material is protected by a nitrogen atmosphere, placed in an environment of 40-80°C and dried for 1-12 hours, and then pressed into a blank, placed in an SPS sintering furnace, protected by an argon atmosphere, and a pressure of 100-1000 kN is applied to the blank, and the temperature is raised to 900-1200°C at a rate of 90-110°C / min, sintered into a block, and then cooled to room temperature with the furnace to obtain a graphene copper alloy original ingot; S12. Mixing the graphene copper alloy ingot with the reinforcing metal material, protecting the ingot with argon atmosphere, heating the induction furnace to 1050-1250°C for melting, stirring and mixing for 10s-15min, and then continuously casting the molten metal into a mother rod with a diameter of 8mm; S13. The mother rod is subjected to multiple drawing and elongation treatments until its diameter is 15-500 μm to obtain a graphene copper alloy core; S2. Preparing a composite coating; S21. Preparing a first palladium layer; Place the cleaned graphene copper alloy core in the first electroplating palladium solution at a temperature of 70-75°C and set the pulse current to 3-5 mA / cm 2 , the on-time of each pulse is 0.5-1s, and the off-time is 0.5-2s. After electroplating to the required thickness of the first palladium layer, the pulse is stopped, the graphene copper alloy core is taken out, and the first palladium layer is formed after washing and drying; S22. Preparing an intermediate gold layer; Place the graphene copper alloy core treated in step S21 in an intermediate gold plating solution at a temperature of 70-80°C, and set the electroplating pulse current to 5-15 mA / cm 2 , the on-time of each pulse is 1.5-3s, and the off-time is 0.5-2s. After electroplating to the required thickness, the pulse is stopped, the graphene copper alloy core is taken out, and after washing and drying, an intermediate gold layer is formed; S23. Place the graphene copper alloy core treated in step S22 in a second palladium electroplating solution at a temperature of 70-80°C and set the current to 10-60 mA / cm 2 , after electroplating to a desired thickness, the graphene copper alloy core is taken out, washed and dried to form a second palladium layer; S24. Place the graphene copper alloy core processed in step S23 in a top layer gold plating solution at a temperature of 70-80°C and set the current to 10-60 mA / cm 2 , after electroplating to a desired thickness, the graphene copper alloy core is taken out, washed and dried, and a top gold layer is formed to obtain a graphene copper alloy core with a composite coating; S3. The graphene copper alloy core with the composite coating is annealed at a temperature of 400-700°C, a furnace length of 600-1000mm, and an annealing speed of 40-140m / min. After the annealing, a high corrosion resistance and high conductivity palladium-plated / gold-plated palladium-copper bonding wire is obtained.

2. The method for preparing a highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire according to claim 1, characterized in that: The diameter of the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire is 15-500 μm, and the thickness of the composite coating is 51-185 nm; The composite coating consists of a first palladium layer, a middle gold layer, a second palladium layer and a top gold layer from bottom to top.

3. The method for preparing the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire according to claim 1, characterized in that: The grain size within the interface of the graphene copper alloy core is 0.1-200 μm; The graphene copper alloy core contains 100-10000ppm of graphene and 5-5000ppm of reinforcing metal material; Among them, the reinforcing metal material is any one or more of Ag, Pd, Au, Pt, Li, P, Ca, Ni, Be, Y, La, Ce, Zr, In, Ge, and Sc.

4. The method for preparing the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire according to claim 1, characterized in that: The graphene copper alloy core contains 300-3000ppm of graphene and 0-3000ppm of reinforcing metal material; The reinforcing metal material is any one or more of Au, Pd, In, P, Ni, Ca, Li, and Sc; When the reinforcing metal material contains any one of P, Li and Sc, the single component addition amount of P, Li and Sc is 0-300ppm.

5. The method for preparing the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire according to claim 1, characterized in that: In the composite plating layer, the thickness of the first palladium layer is 10-20nm, the thickness of the middle gold layer is 20-80nm, the thickness of the second palladium layer is 20-80nm, and the thickness of the top gold layer is 1-5nm.

6. The method for preparing the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire according to claim 1, characterized in that: The method for preparing the graphene copper mixed material comprises the following steps: a1. Prepare electrolyte; Copper sulfate, sulfuric acid and deionized water are mixed to prepare a mixed solution with a sulfuric acid concentration of 10-200 g / L and a copper ion concentration of 10-100 g / L, 1-20 g / L of graphene is added to the electrolyte, and the graphene is evenly dispersed by electromagnetic stirring and ultrasonic dispersion to obtain an electrolyte; b1. Use high-purity copper with impurity element content of 0-10ppm as anode and pure copper plate as cathode for electroplating. The voltage is 2-10V and the current density is 1-10mA / cm 2 After 10-60 minutes of electro-deposition, the cathode is taken out and washed with deionized water, and the graphene copper powder on the cathode surface is collected and dried. After XPS detection, it is determined that the carbon-copper bond ratio is 35-45%, and then it is mixed with oxygen-free copper powder. After that, it is melted evenly in an argon atmosphere, cooled, and XPS detection is performed again. After determining that the carbon-copper bond ratio is 3-5%, it is mixed with pure copper powder again. After melting evenly, it is crushed by ball milling to obtain a graphene copper mixed material.

7. The method for preparing the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire according to claim 1, characterized in that: The method for preparing the graphene copper mixed material comprises the following steps: a2. Disperse the graphene in ultrapure water, stir and ultrasonically disperse and wash for 0.5-1h, then filter and filter, repeat 2-3 times, detect the pH value of the filtrate, confirm that the pH value is in the range of 6.3-7 for qualified cleaning, otherwise repeat the above steps to wash the graphene with ultrapure water until the pH value of the filtrate is qualified, dry the washed graphene in a nitrogen atmosphere, cool and set aside; b2. After the cleaned graphene is mixed with high-purity oxygen-free copper powder, low-temperature plasma ball milling is performed for 3-24 hours. The speed during ball milling is 100-1200rpm, the protective gas is nitrogen, and the plasma working power is 10-400W. After the ball milling, a graphene-copper mixed material is obtained.

8. The method for preparing the highly corrosion-resistant and highly conductive palladium-plated / gold-plated palladium-copper bonding wire according to claim 1, characterized in that: The first palladium electroplating solution comprises palladium tetraaminoacetate, p-carboxybenzenesulfonamide and a composite hole-filling agent; Wherein, in the first palladium electroplating solution, the concentration of palladium tetraaminoacetate is 3-5 g / L, the concentration of p-carboxybenzenesulfonamide is 5-15 mg / L, and the concentration of the composite pore filling agent is 25-55 mg / L; The composite pore-filling agent is a composition of diethyl dithiophosphate ammonium salt and L-alanine benzyl ester p-toluenesulfonate in a mass ratio of 1:1; The second palladium electroplating solution comprises tetraaminopalladium dichloride, p-carboxybenzenesulfonamide and β-cyanoalanine; Wherein, in the second palladium electroplating solution, the concentration of tetraaminopalladium dichloride is 5-10 g / L, the concentration of p-carboxybenzenesulfonamide is 5-10 mg / L, and the concentration of β-cyanoalanine is 10-20 mg / L; The intermediate gold plating solution includes gold cyanide and a composite hole filling agent; Among them, in the intermediate gold plating solution, the concentration of gold cyanide is 4-8g / L, and the concentration of the composite hole filling agent is 50-80mg / L; The top layer gold plating solution includes gold cyanide, and the concentration of gold cyanide is 5-15g / L; Wherein, when the intermediate gold plating solution and the top layer gold plating solution are used, the pH value is adjusted to 10-12 by ammonia water.

Citation Information

Patent Citations

  • Production method of modified copper bonding wire

    CN115921871A

  • Copper-plated palladium-gold bonding wire and electroplating process thereof

    CN116657207A

Cited By

  • Corrosion-resistant gold-plated palladium copper wire and preparation method and application thereof

    CN121344596A